Resilience and occupational education: an approach to nursing at the Material and Sterilization Center (Research, Society and Development, 2021)
Objective: To point out Permanent Health Education as an instrument of awareness for managers, nursing coordination and other professionals about the institutional and social benefits of an active educational process. Methodology: exploratory, qualitative approach, setting the material center and sterilization of a university hospital. The participants, 31 of the nursing staff: 03 nurses, 16 technicians and 12 nursing assistants. Results: subjected to content analysis unveiling three categories: Disaggregation; Invisibility and Coping. Conclusion: reorienting in a multidirectional way, the perception about the specificities of workers, despite the relevance of professional performance, is not seen, due to interpersonal ties restricted to confined work, Permanent Health Education, due to the inter and multiprofessional approach, appears as an instrument capable of producing changes in work practices and contexts, since the failure of resilient behavior can be alienation or biopsychosocial disorders. Other approaches are required.